Individual criminal responsibility in international law - Sliedregt, E. van. (Oxford : Oxford University Press, 2012)
Atrocities such as genocide or crimes against humanity are usually committed by a large number of perpetrators. Moreover those who masterminded the crimes may not have actively participated. This book sets out how these people can be held responsible for their crimes by international criminal tribunals.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Criminal liability (International law); Crimes against humanity